Pengaruh Penerapan Akuntansi Pemerintahan Berbasis Akrual, Kompetensi Sumber Daya Manusia dan Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah pada Dinas Komunikasi Informatika dan Statistik Provinsi Lampung - Eka Putri, Aprilia; Sekar Sari, Meita; Khoirina, Siti (HUMAN: Journal of Social Humanities and Science, 2023)
The purpose of this study was to determine how much influence the Application of Accrual-Based Government Accounting Standards, Competence of Human Resources and Internal Control has on the Quality of Government Financial Reports. In this study using a quantitative descriptive approach where data processing is done statistically. The number of samples taken was 104 respondents using the Saturated Sampling method, the group from Non Probability Sampling, which was carried out by census where the population was used as a sample which was registered at the Lampung Province Information and Communications Office. The data source in this study is primary data obtained using a questionnaire which is then processed by multiple linear analysis tests using SPSS version 21. The results of this study indicate that the Application of Accrual-Based Government Accounting Standards, Human Resource Competence and Internal Control simultaneously and partially positive and significant effect on the Quality of Government Financial Statements.